Pengaruh Digital Leadership, Total Quality Management, dan Knowledge Management terhadap Sustainability Management pada Perusahaan di DKI Jakarta - Jennifer Wesly; Veren Kristiana; Tommy Bong; Nopriadi Saputra (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: This study aimed to determine the influence of digital leadership, total quality management, and knowledge management on companies’ sustainability management in DKI Jakarta. Research methodology: The sampling technique used in this research is the convenience sampling technique. It used primary data through questionnaire distribution with 389 respondents of employees who work in DKI Jakarta. As for the data analysis technique, this research used the regression technique in both simple and multiple regression. Results: The results of this study indicate that digital leadership and knowledge management have a significant influence on the sustainability management of companies in DKI Jakarta. Meanwhile, total quality management does not have a significant influence on the sustainability management of companies in DKI Jakarta Limitations: This study only examines the variables of digital leadership, total quality management, knowledge management, and sustainability management. This research is also limited to employees who work at companies in DKI Jakarta. Contribution: This study shows how the level of digital leadership, total quality management, knowledge management, and sustainability management in companies in DKI Jakarta. This study also shows how digital leadership, total quality management, and knowledge management affect sustainability management. Companies can use this research to improve the company’s sustainability management by implementing digital leadership, knowledge management and paying more attention to the importance of developing total quality management within the company.